An Operational Geomagnetic Baseline Derivation Method for Magnetic Observatories Located in Mid‐Latitudes - Veronika Haberle; Aurélie Marchaudon; Aude Chambodut; Pierre‐Louis Blelly (Space Weather)
Abstract Ground magnetic field measurements are an important tool to determine the strength of space weather events in the terrestrial environment on local and global scales. For that purpose, geomagnetic baselines play a vital role as they describe typical quiet variations within geomagnetic data which allows the successive isolation of magnetic storm contributions. This work introduces an operational baseline derivation method to accurately assess then replace the amplitude of space weather events within high‐quality ground magnetic field measurements from magnetic observatories located in mid‐latitudes. A two‐step approach first identifies storm and disturbance intervals within the magnetic signal. Quiet variations, consistent with pre‐ and post‐disturbance periods, are then used to replace the signal during the identified intervals. The final baseline is validated through comparisons with existing methods and through demonstration during moderate and strong space weather events at 13 globally distributed observatories, demonstrating its ability to track quiet variations accurately while maintaining them during disturbances. This supports the application of the introduced baseline for geomagnetic field description and new magnetic index derivation for space weather event characterization with high spatio‐temporal resolution. As the method is deployable in near real‐time, it is suitable for operational environments.